Análisis Y Diseño De Una Aeronave No Tripulada Para Uso Agrícola - Chávez, Javier Enrique Orna; Sampedro, Otto Fernando Balseca; Reyes, Jorge Isaías Caicedo; Pérez, Diego Fernando Mayorga; Núñez, Edwin Fernando Viteri; Bernal, Catalina Margarita Verdugo (European Scientific Journal, ESJ, 2017)
The present research proposes to diversify the use of unmanned aerial vehicles (UAV) with rotating wings for applications in the agricultural sector. For this we have analyzed and designed an unmanned aircraft. In first instance the applications of this type of aircraft in this sector were reviewed to determine possible design conditions that would aid in the sizing and design of the aircraft. Once the requirements had been determined, aerodynamic analysis was carried out to size up and launch the required power output for the craft. This in order to optimize the weight and autonomous fight time to finally design an aircraft prototype built in carbon fiber with the aid of fault theories as applied to composite materials. At the end of the research, an unmanned aircraft of 6 rotors, each with an installed power supply of 700W was designed. The aircraft has an autonomous flight time of 40 minutes without a payload, 20 minutes with a payload of 3Kg, and 8 minutes with a payload of 5Kg. The commercial application of these aircraft are the monitoring of land and fumigation in inaccessible areas.